Safety evaluation of mice exposed to 7.0–33.0 T high‐static magnetic fields. Issue 6 (31st December 2020) - Tian, Xiaofei; Lv, Yue; Fan, Yixiang; Wang, Ze; Yu, Biao; Song, Chao; Lu, Qingyou; Xi, Chuanying; Pi, Li; Zhang, Xin
Abstract: Magnetic resonance imaging (MRI) of 7 T and higher can provide superior image resolution and capability. Clinical tests have been performed in 9.4 T MRI, and 21.1 T small‐bore‐size MRI has also been tested in rodents. Although the safety issue is a prerequisite for their future medical application, there are very few relevant studies for the safety of static magnetic fields (SMFs) of ≧20 T. The aim of this study was to assess the biological effects of 7.0–33.0 T SMFs in healthy adult mice. This was a prospective study, in which 104 healthy adult C57BL/6 mice were divided into control, sham control, and 7.0–33.0 T SMF‐exposed groups.The sham control group and SMF group were handled identically, except for the electric current for producing SMF. A separate control group was placed outside the magnet and their data were used as normal range. After 1 h exposure, all mice were routinely fed for another 2 months while their body weight and food/water consumption were monitored. After 2 months, their complete blood count, blood biochemistry, key organ weight, and histomorphology were examined. All data are normally distributed. Differences between the sham and SMF‐exposed groups were evaluated by unpaired t test. Most indicators did not show statistically significant changes or were still within the normal ranges, with only a few exceptions. For example, mono % in Group 2 (11.1 T) is 6.03 ± 1.43% while the normal range is 6.60–9.90% ( p  < 0.05). The cholesterol level in 33 T group is 3.38 ± 0.36 mmol/L while the normal range is 2.48–3.29 mmol/L ( p  < 0.05). The high‐density lipoprotein cholesterol level in 33 T group is 2.54 ± 0.29 mmol/L while the normal reference range is 1.89–2.43 mmol/L ( p  < 0.01). Exposure to 7.0–33.0 T for 1 h did not have detrimental effects on normal adult mice. Level of Evidence: 1 Technical Efficacy Stage: 1